2023
DOI: 10.5812/gct-131147
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative Effect of Satureja sahandica Extraction by Co-administration of Layered Double Hydroxide (LDH) Nanosheets on HepG2 Hepatocellular Carcinoma Cell Line

Hafez Abdol,
Leila Taghipour,
Saber Raeghi
et al.

Abstract: Background: Hepatocellular carcinoma (HCC) is a common solid tumor and the third cause of cancer death worldwide. Resistance to chemotherapeutic drugs is a serious challenge in the treatment of HCC. To address this challenge, therefore, attempts have been made to develop novel anticancer agents by using medicinal plants and producing novel natural chemical compounds. Objectives: This study aimed to investigate the anti-proliferative effect of the Satureja sahandica extraction combined with layered double hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The reduction in cell motility was accompanied by the downregulation of mesenchymal markers involved in EMT, such as CDH-2, Snail-1, and ZEB-1 (at mRNA level). In line with our results, Abdol et al indicated that S. sahandica extraction significantly decreased the migration of cancer cells in a concentration-dependent manner [38]. Although there are few studies on the effect of the Satureja species on cancer cell migration and invasion, many researchers have studied the effect of polyphenolic components of this species on cell migration and invasion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reduction in cell motility was accompanied by the downregulation of mesenchymal markers involved in EMT, such as CDH-2, Snail-1, and ZEB-1 (at mRNA level). In line with our results, Abdol et al indicated that S. sahandica extraction significantly decreased the migration of cancer cells in a concentration-dependent manner [38]. Although there are few studies on the effect of the Satureja species on cancer cell migration and invasion, many researchers have studied the effect of polyphenolic components of this species on cell migration and invasion.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, in another study, Esmaeili-Mahani et al reported that S. khuzestanica extract induced apoptosis and prevented cell division in human breast cancer cells (MCF-7) [37]. Abdol et al also reported similar results in which S. sahandica treatment led to the induction of apoptosis in hepatocellular carcinoma cell lines by regulation of apoptosis-related genes BAX and BCL2 [38]. So far, no study has reported the effect of the Satureja genus on the growth of cells in a 3D culture model; our data reveal for the first time that S. bachtiarica reduces the growth of spheroids compared to the control group.…”
Section: Discussionmentioning
confidence: 84%